-x+3x-2=0

Simple and best practice solution for -x+3x-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+3x-2=0 equation:


Simplifying
-1x + 3x + -2 = 0

Reorder the terms:
-2 + -1x + 3x = 0

Combine like terms: -1x + 3x = 2x
-2 + 2x = 0

Solving
-2 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 2x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 2x = 0 + 2
2x = 0 + 2

Combine like terms: 0 + 2 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| 9+3=612*x | | -1.23x=-456 | | 16x+3=18x+2 | | 2q=26 | | 11x=7x+12 | | 9+3+x=612*x | | 0.1x+0.5y=-1.3 | | 3(x-7)+20=-2+6x+1 | | 16x+3=18+2 | | 8a-7=7+a | | 3x-8=2+X | | 9+3+x=612 | | -11+19x=19x-11 | | 1.5d+8.25=3+3.25d | | 15b=a | | 2t-7=t-2 | | h+9.2=-9.2 | | -5p+39=14 | | 3-10b=2b-a | | 2x-11+3x-14=15 | | 8(10x-10)=85x+500 | | 3(x-4)+7x=24+x | | 3(x-1)=4x+8 | | 7x-13=x+8 | | 8v-6v=10 | | 4(r-8)=8(r-5) | | 5-3n=41 | | -2-x=10 | | -(-2x-4)+5=26 | | 24-2w=33 | | 22-30=x | | 5x-8y=-11 |

Equations solver categories